Selective Mutism in Elementary School Children: Do Gadgets Play a Role? - Ubaidillah, Sofwan Roiif; Usriyah, Lailatul; Mu’allimin, Mu’allimin (IJIE International Journal of Islamic Education, 2024)
This study analyzes the phenomenon of selective mutism in elementary school children and the role of gadget use in influencing the condition. Selective mutism is an anxiety disorder characterized by the inability of children to speak in certain environments, such as school, although they can communicate fluently in more familiar environments. Excessive use of gadgets is known to worsen selective mutism because it reduces direct social interaction, increases levels of social anxiety, and interferes with children's concentration. The purpose of this study was to identify the causes of selective mutism and evaluate the impact of gadget use on the disorder. Using a qualitative approach through interviews and observations of students at SDN Kaliwates 01 Jember, this study explored the factors that influence selective mutism, especially in relation to the impact of gadgets on increasing anxiety and limited communication in children. The results showed a relationship between gadget use and increased symptoms of selective mutism. Support from parents and schools was found to have a crucial role in regulating gadget use and improving children's social skills. This study recommends limiting gadget use and children's participation in social activities as an effort to help them gradually overcome selective mutism and build confidence in communicating in a wider social environment.